SARS-CoV-2 Variant Determination Through SNP Assays in Samples From Industry Workers From Rio de Janeiro, Brazil - Henriques-Santos, Bianca Monteiro; Farjun, Bruna; Corrêa, Isadora Alonso; Figueiredo, Janaina de Barros; Fidalgo-Neto, Antonio Augusto; Kuriyama, Sergio Noboru (Frontiers in Microbiology, 2022)
Since the first reported case in December 2019, SARS-CoV-2 infections became a major public health worldwide. Even with the increasing vaccination in several countries and relaxing of social distancing measures, the pandemic remains a threat especially due to the emergence of new SARS-CoV-2 variants. Despite the presence of an enzyme capable of proofreading its genome, high rates of replication provide a source of accumulation of mutations within viral genome. In this retrospective study, samples from a cohort of industry workers tested by the SESI’s COVID-19 mass testing program from September 2020 to May 2021 were analyzed using a mutation panel in order to describe the circulation of currently identified SARS-CoV-2 variants within the samples obtained in Rio de Janeiro State. Our results demonstrated that the VOI Zeta has been in circulation since October 2020 and reached 87% of prevalence in February 2021 followed by a decrease due to emergence of Gama VOC. Gama was detected in January 2021 in our studied population and its prevalence increased during the following months reaching absolute prevalence within positive samples in May. The Alpha variant was detected only in 4-7% of samples during March and April while Beta VOC was not detected in our study. Our data agrees with sequencing genomic surveillance databases and highlights the importance of continuous mass testing programs and variant detection in order to control viral spread and guide public health measures.